EARLY MOBILIZATION PADA PASIEN OSTEOARTHRITIS KNEE DENGAN POST TOTAL KNEE REPLACEMENT: NARRATIVE REVIEW - Bernardus Edwin Dewantoro; Noraeni Arsyad; Zeth Boroh (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Background: Total knee replacement (TKR) is a common orthopedic surgical procedure for advanced knee osteoarthritis (OA). Early mobilization is a rehabilitation strategy that needs to be considered to facilitate optimal recovery post-TKR. Despite the proposed benefits of early mobilization, there is no strong consensus in the literature regarding its effectiveness in post-TKR patients. Therefore, it is important to conduct a comprehensive literature review to evaluate existing evidence on the impact of early mobilization on post-TKR recovery. This will help strengthen understanding of the benefits and influencing factors on post-TKR rehabilitation outcomes. Method: This study is a qualitative research with a narrative review approach. Article searches were conducted using the online databases EBSCO, SCOPUS, ProQuest, and ScienceDirect. Literature identification was performed using the PICO search strategy. Results: The initial search with full-text articles yielded 4153 articles. Study selection was based on pre-established inclusion and exclusion criteria, resulting in 20 final articles that will be qualitatively synthesized. Conclusion: Early mobilization is significantly associated with a reduction in the length of stay for post-TKR patients. Mobilization starting from day 0 of the operation will shorten the hospitalization duration. Additionally, early mobilization has been proven to decrease the risk of complications, thereby preventing prolonged care.